PELESTARIAN KESENIAN SINGA DEPOK JATIROKE SEBAGAI PEMERTAHANAN BUDAYA LOKAL - Susanti, Santi; Esih, Suka (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Adapted by the Jatiroke Village society with certain reasons. This paper aims to express the socio-cultural values ​​contained in Singa Depok art developed in RW 03 Jatiroke Village. Based on the interview with the manager of Jatiroke Singa Depok Art, the beginning of Singa Depok Art in Jatiroke aims to avoid the emergence of negative actions due to the large number of unemployed people. The presence of Singa Depok Art is expected to strengthen togetherness of the people of Jatiroke Village, especially the youth. Singa Depok Jatiroke was displayed in a number of festivals, carnivals, children's birthdays, sub-district events and the Sumedang district's birthday. The figure of the Jatiroke artist hopes that through the art of Singa Depok, its citizens can fill their daily activities with productive activities so that they are together and create a safe and peaceful environment.